2016
DOI: 10.1093/nutrit/nuv065
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein intake on body composition changes after weight loss in older adults: a systematic review and meta-analysis

Abstract: The impact of dietary protein on body composition changes after older adults purposefully lose weight requires systematic evaluation. Objective: This systematic review and meta-analysis assessed the effects of protein intake (<25% vs !25% of energy intake or 1.0 g/kg/d) on energy restriction-induced changes in body mass, lean mass, and fat mass in adults older than 50 years. Data Sources: PubMed, Cochrane, Scopus, and Google Scholar were searched using the keywords "dietary proteins," "body composition," "skel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(135 citation statements)
references
References 66 publications
11
118
1
5
Order By: Relevance
“…(2) This finding on protein’s role in maintaining lean mass was supported by another meta-analysis focusing on 24 trials conducted specifically in older adults (>50 yrs). (7) In DiOGenes, at both the 6- and 12-month maintenance follow-ups, weight regain was lower in the high-protein (25% of energy) than in the low-protein (13% of energy) groups, and high-protein groups were more likely to achieve additional weight loss in the follow-up period. (56,57) In a recent re-analysis of DiOGenes investigating plant and animal protein sources, while substituting overall plant for animal protein was not associated with effects on body weight, higher plant protein specifically in the form of non-cereal sources vs. cereal-based sources was favorably associated with body weight changes.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(2) This finding on protein’s role in maintaining lean mass was supported by another meta-analysis focusing on 24 trials conducted specifically in older adults (>50 yrs). (7) In DiOGenes, at both the 6- and 12-month maintenance follow-ups, weight regain was lower in the high-protein (25% of energy) than in the low-protein (13% of energy) groups, and high-protein groups were more likely to achieve additional weight loss in the follow-up period. (56,57) In a recent re-analysis of DiOGenes investigating plant and animal protein sources, while substituting overall plant for animal protein was not associated with effects on body weight, higher plant protein specifically in the form of non-cereal sources vs. cereal-based sources was favorably associated with body weight changes.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, higher protein intake is thought to be more beneficial in older individuals, potentially delaying age-related muscle loss and other cardiometabolic abnormalities. (7,1417) However, there is still conflicting evidence regarding the longer-term effects of high protein intake on other cardiometabolic health parameters related to aging. Some prospective cohort studies have indicated that higher habitual protein intake increases risk of cardiometabolic endpoints, such as diabetes and metabolic syndrome (1822) , and mortality (14,18,19) , particularly in the context of low carbohydrate intake.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reports that using gelatin as a single diet protein results in appetite suppression in adults, which is more significant than using casein 26. A recent review that investigated the effects of dietary protein intake on body composition changes also indicates that consuming high-protein diets contributes to the maintenance of lean mass and the loss of fat mass during weight loss in older adults 27. Our findings indicate that supplementing with collagen hydrolysate, the digested gelatin, attenuates body weight gain and adipocyte enlargement in OVX rats.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited between 16 March 2017 and 12 April 2017 via the Nijmegen Exercise Study database (Study‐ID: NL36743.091.11) and social media. Interested men and women of at least 65 years old were included if they (i) had a habitual protein intake ≤1.0 g/kg/day based on a 123 item online food frequency questionnaire calculated using the Dutch Food composition database of 2010, (ii) were registered and in training for the 2017 Nijmegen Four Days Marches [an annual 4 day walking event (30, 40, or 50 km/day) in the Netherlands; https://www.4daagse.nl/en], and (iii) were able to understand and perform the study procedures. Exclusion criteria for participation in the study were type 1 or type 2 diabetes mellitus (non‐fasted state >11 mmol/L), allergic or sensitive for milk proteins or lactose intolerant, Chronic Obstructive Pulmonary Disease (COPD), cancer, renal insufficiency [estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m −1 ], intestinal diseases that may influence the uptake of protein, use of statins, and involved in a heavy resistance type exercise programme.…”
Section: Methodsmentioning
confidence: 99%